We have y = (sin x)/ x

=> y = (x^-1) * (sin x)

y' = x^-1 * cos x + sin x * (-1)*x^-2

=> y' = (cos x)/x - (sin x)/x^2

The required value of dy/dx = (cos x)/x - (sin x)/x^2

At a stationary point we have...

## Check Out

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have y = (sin x)/ x

=> y = (x^-1) * (sin x)

y' = x^-1 * cos x + sin x * (-1)*x^-2

=> y' = (cos x)/x - (sin x)/x^2

The required value of dy/dx = (cos x)/x - (sin x)/x^2

At a stationary point we have dy/dx = (cos x)/x - (sin x)/x^2 = 0

(cos x)/x - (sin x)/x^2 = 0

=> x*(cos x) = sin x

=> x = (sin x)/(cos x)

=> x = tan x.

**It is thereby proved that x = tan x at the stationary points of the curve y = (sin x)/x**